The role of alcohol and other drugs on emergency department traumatic injury mortality in the United States. (1st August 2021) - DiMaggio, Charles J.; Avraham, Jacob B.; Frangos, Spiros G.; Keyes, Katherine
Highlights: Alcohol and substance-related emergency department visits increased during a recent 7-year study period. Alcohol and substance abuse does not offer a protective benefit in the setting of trauma, as has previously been suggested. Alcohol and substance abuse may increase the risk of death related to traumatic injury. Abstract: Background: Alcohol and other drugs (AOD) increase the risk of traumatic injury occurring, but data suggest a protective benefit in preventing trauma-related mortality. The objective of this study is to describe the epidemiology of AOD-related traumatic injury in the US over a recent 7 year period and assess the interaction of traumatic injury and AOD on pre-admission fatality on both an additive scale using incidence contrasts and on a statistical multiplicative scale using survey-adjusted logistic regression. Methods: Using the National Emergency Department Sample (NEDS), we describe the epidemiology of alcohol and substance-related emergency department traumatic injury over a recent period. AOD-related injury was assessed using survey-adjusted counts and means. Ratio estimates and differences were calculated using simulations based on survey-adjusted counts and standard errors. Differences in trends over time were evaluated by comparing the slopes of linear regression equations with year as the predictor variable. Results: Alcohol and substance-related emergency department injury discharges increased 9.8 % during the study period. There was a statistically significant interaction between traumatic injury death and AOD on both an additive scale and multiplicative scale. (Odds Ratio for interaction term = 1.76, 95 % CI = 1.53, 2.03). Conclusions: AOD use does not provide a protective benefit in the setting of trauma, but rather is an important contributor to traumatic injury mortality.